Stephen Hawking's universe : seeing is believing - the big bang [1-2] - Hawking, S. W.; Filkin, David; Martin, Philip, 1938-; Langella, Frank; WNET (Television station : New York, N.Y.); Uden Associates; David Filkin Enterprises; British Broadcasting Corporation. Television Service; Public Broadcasting Service (U.S.); Warner Home Video (Firm) (Burbank, Calif. : Warner Home Video, 1997)
Program 1: Knowledge of the universe is built on the foundations laid down by thousands of years of scientific inquiry. This program explores mathematics and how it revolutionized our view of the universe. Recollect Ptolemy's theory of the motion of the planets, moon and sun; Newton's picture of the universe governed by gravity; Einstein's revolutionized theory of physics and Hubble's invention of the telescope that saw the expansion of the universe.
Program 2: When and how did the universe begin? Scientists have developed two theories: the Big Bang and the Steady State theories. This program explores the search for evidence to support the Big Bang theory of the origin of the universe. It highlights the contributions and theories of Albert Einstein, Georges Lemaitre, Fred Hoyle, Arno Penzias, and Robert Wilson.
Special features: Full-motion selection menu screens.
Originally produced for PBS television program Stephen Hawking's universe in 1997.
Narrator: Frank Langella.
DVD.
Keywords: Hawking, S. W; Ptolemy, -- 2nd cent; Newton, Isaac, -- 1642-1727.; Einstein, Albert, -- 1879-1955.; Hubble, Edwin Powell, -- 1889-1953.; Hawking, S. W. -- Views on cosmology; 1894-; Hoyle, Fred; Penzias, Arno A; Wilson, Robert, -- 1928-; Cosmology; Big bang theory; Expanding universe; Celestial mechanics; Astronomy -- Mathematics; Cosmology -- Mathematics